Molecular phylogeny of horseshoe crab - Yunus, Kamaruzzaman; John, Akbar; Kasim, Zaleha; Khan Chowdhury, Ahmed Jalal (Knowledgia Review, Malaysia, 2011)
An effort to assess the utility of 650 bp Cytochrome C oxidase subunit I (DNA barcode) gene in delineating the members horseshoe crabs (Family: xiphosura) with closely related sister taxa was made. A total of 33 sequences were extracted from National Center for Biotechnological Information (NCBI) which include horseshoe crabs (Class: Merostomata), beetles (Class: Insecta), common crabs (Class: Melacostraca) and scorpion (Class: Arachnida) sequences. Constructed phylogram through comprehensive dry lab methodology using advanced software predictive tools showed that beetles are closely related with horseshoe crabs than common crabs (Class: Melacostraca). It was interesting to note that terrestrial Scorpion (Class: Arachnida) were distantly related to horseshoe crabs (Class: Merostomata). Phylogram and observed Genetic Distance (GD) data were also revealed that Limulus polyphemus was distantly related to all the other horseshoe crab species. Tachypleus gigas was closely related with Carcinoscorpius rotundicauda than with Tachypleus tridentatus. The observed mean Genetic Distance (GD) value was higher in 3rd codon position in all the selected group of organisms. Among the horseshoe crabs high GC content was observed in L. polyphemus (38.32%) and lowest was observed in T. tridentatus (32.35%). We conclude that COI sequencing (barcoding) could be used in identifying and delineating evolutionary relatedness with closely related species